2001
DOI: 10.4049/jimmunol.166.3.1855
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Protein-Specific Monoclonal Antibodies Protect SCID Mice from Fatal Infection by the Obligate Intracellular Bacterial Pathogen Ehrlichia chaffeensis

Abstract: Previous studies of Ehrlichia chaffeensis infection in the mouse have demonstrated that passive transfer of polyclonal Abs from resistant immunocompetent mice to susceptible SCID mice ameliorated infection and disease, even when Abs were administered during established infection. To identify particular Abs that could mediate bacterial clearance in vivo, E. chaffeensis-specific mAbs were generated and administered to infected SCID mice. Bacterial infection in the livers was significantly lowered after administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(35 citation statements)
references
References 41 publications
3
32
0
Order By: Relevance
“…Previous studies in our laboratory and elsewhere have demonstrated that P28-19 is the most efficient and protective P28 paralog which provides protection against Ehrlichia [18], [19].…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Previous studies in our laboratory and elsewhere have demonstrated that P28-19 is the most efficient and protective P28 paralog which provides protection against Ehrlichia [18], [19].…”
Section: Resultsmentioning
confidence: 68%
“…Studies from our laboratory and others have previously demonstrated the importance of antibodies in protection against Ehrlichia . Passive transfer of polyclonal immune sera or mAbs confers protection in SCID mice against E. muris and E. chaffeensis , respectively [18], [32]. Prior studies in mouse models have demonstrated that vaccination with P28 leads to immunity and clearance of Ehrlichia infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in an effort to find the protective mechanism mediated by a C. burnettii phase I vaccine (PI-V) strain, Zhang et al demonstrated that a switched IgG response to PI-V lipopolysaccharide (LPS) provided significant protection to the host to an extent comparable to PI-V vaccination against C. burnetii infection [68]. Similar observations have also been made in obligate intracellular Ehrlichia chaffeensis infections, where antibody recognizing the major outer membrane protein (OMP)-1g of E. chaffeensis protects SCID mice from ehrlichiosis, a vector-borne disease [69]. …”
Section: B Cells and Intracellular Infections: Lesson Learned Frommentioning
confidence: 96%
“…Although E muris was originally described as a mouse pathogen, a closely related, if not identical pathogen, has been shown to infect humans (known as the E. muris -like agent, or EMLA; [4]). As an obligate intracellular pathogen, E. muris cannot replicate outside of host cells, although we have reported that the bacteria can be found extracellularly [5], a property that is presumably necessary to facilitate blood-borne transmission, and which at the same time may predispose the bacteria to clearance by antibodies [6]. E. muris infection, which is not fatal in immunocompetent mice and humans, nonetheless causes a number of clinical manifestations, including anemia, thrombocytopenia, splenomegaly, as well as hematological alterations, including myelopoiesis and perturbation of the hematopoietic stem cell niche [7].…”
Section: Discovery Of Cd11c+ B Cellsmentioning
confidence: 99%